ASSESSMENT OF THE INFLUENCE OF CRACKING ON THE FRACTURE ENERGY OF BRITTLE MATERIALS USING NUMERICAL MODELING - HMYZA, VALERII; VOROBYOV, VICTOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In the field of geomechanics and brittle material engineering, the presence of internal or surface defects plays a significant role in the structural behavior of rocks and other hard media. This study focuses on quantifying the effect of such defects—primarily artificial fractures and voids—on the amount of energy required for material destruction under impact loading. Numerical simulations were performed using the ANSYS Explicit Dynamics software environment to examine the behavior of specimens composed of gypsum G-5 and concrete, both with and without internal defects. A series of controlled impact experiments was simulated to compare the energy required to fracture intact samples and those containing geometrically defined defects such as central voids, side cracks, and edge notches. The study also demonstrated that the length, orientation, and placement of the cracks have a measurable influence on the crack propagation and ultimate failure pattern of the specimen. This article provides a practical numerical framework to visualize and quantify how the presence of defects affects the mechanical integrity of brittle materials. The findings of this study can be used as a basis for further investigations in the design and safety assessment of geotechnical structures such as quarry benches, underground supports, and brittle engineered materials.